Primary Osteosarcoma of the Breast: A Case Report - Anna Rizzi; Alberto Soregaroli; Claudia Zambelli; Fausto Zorzi; Stefano Mutti; Claudio Codignola; Paola Bertocchi; Alberto Zaniboni (Case Reports in Oncological Medicine)
Introduction. Primary osteosarcoma of the breast is a rare soft-tissue form of osteosarcoma without involvement of the skeletal system. Due to the rarity of the disease, its clinical features and optimal treatment remain unclear. Case Presentation. This case report deals with a 62-year-old woman with pure osteosarcoma of the breast. Conclusions. The prognosis of primary osteosarcoma of the breast is poor. Recurrence is frequent, and it is often associated with haematogenous spread of the disease to the lung. Treatment follows the model of sarcomas affecting other locations and must be planned in a multidisciplinary fashion. Adjuvant chemotherapy should be considered for patients with tumors showing aggressive features.